VENO-ARTERIAL BYPASS OF CENTRIFUGAL PUMP WITHOUT AN OXYGENATOR ON THE DESCENDING THORACIC AORTA CLAMPING - UWATOKO, T.; KATO, R.; TSUCHIOKA, H.; ASAI, T.; OHTA, T.; KAZUI, H.; HOSAKA, M.; BOKU, K.; IKEUCHI, K.; KONDP, M. (Jinko Zoki, 1990)
Ten dogs were examined for surgery of the descending thoracic aorta clamping with simplified veno-arterial bypass (V-A bypass) using a centrifugal pump (Bio-pump) without oxygenator. Bypass route was made between SVC or the right atrium and the femoral artery. Aorta clamping time was set at 2 hours. Blood gas, blood pressures at proximal and distal sides of aortic clamp and urinary output were examined. All dogs survived 1to2 weeks and were referred laboratory data to the sacrificial death. Controlled study was done by left heart bypass (A-A bypass) between the left atrium and the femoral artery in 4 dogs. In the V -A bypass group, PaO2 and O2 saturation of perfusion blood were 59±24mmHg (21-129mmHg) and 83±14% (33-99%), respectively. Laboratory data were not significantly different from those of the left heart bypass group. The results show that V-A bypass with centrifugal pump is suitable for assist circulatim during descending thoracic aorta clamping.